Physico-technical fundamentals of creating a composite material (concrete) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article is devoted to the physical and technical basics of creating a composite material (concrete). The object of the study is concrete made on the basis of quartz sand from the Ozgur deposit, the subject of the study is to determine the strength, water resistance and frost resistance of concrete. A mathematical model has been created, as well as a computer model for calculating the strength, water resistance and frost resistance of concrete using input data such as the ratio of cement to water, the ratio of sand to crushed stone, ambient temperature, moderate temperature time, cement hydration coefficients, coefficients of interaction of the binder with the filler and the coefficient of concrete maturation. This model allows you to ensure the strength, manufacturability and frost resistance of concrete, depending on its composition and operating conditions. The developed mathematical model with software can be used in construction companies for the design and production of concrete.
Keywords: Composite material, concrete, quartz sand, concrete strength, concrete durability, concrete workability, frost resistance, concrete water resistance.